A STUDY ON PERSONALITY TYPE AND TOURISM EXPECTATIONS OF LOCAL PEOPLE: THE CASE OF UZBEKISTAN-KOKAND (American Journal of Business Management, Economics and Banking, 2025)
One of the most important aspects in the development of tourism in a region is to learn the expectations of the local people, who are the stakeholders of the sector. Because tourism has economic, social and environmental effects on the local people and when these effects are not managed properly, negative effects may arise due to improperly managed tourism plan. For this reason, it is an important that the views of the local people should be taken into account for the development of tourism in a region. In this study, which was designed with this thought in mind, the tourism expectations of the local people of Kokand, which is believed to have potential opportunities for tourism growth in Uzbekistan, are approached in terms of personality types and it is aimed to support tourism development. In the scope of the study, a questionnaire was applied to 422 participants within the scope of easy sample management, in the period of January-April 2023. As a result of the analysis of the survey data, it has been determined that the expectations of the local people is associated with the sub-dimensions of quality of life, natural environment-regional development, tourism infrastructure and tax income.